Temporal Focus and Innovativeness of Consumers in the Use of Technologies: A Cross-Cultural Study - Cruz-Cárdenas, Jorge (2021)
nnovative consumers are very important to today’s businesses as they are the first adopters of new products. This article seeks to contribute to the existing knowledge on the characteristics and traits that innovative consumers possess by focusing on the temporal orientation of said consumers. The current study is a cross-cultural study based on a survey that was carried out in Ecuador (a South American developing country) and Russia (a Eurasian emerging country). The results obtained for the two countries consistently establish that the temporal focus in the future is a characteristic associated with innovative consumers. The current study also presents the theoretical and practical implications of these findings.